If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 8r + -3 = 7r + 29 + -3r Reorder the terms: 4 + -3 + 8r = 7r + 29 + -3r Combine like terms: 4 + -3 = 1 1 + 8r = 7r + 29 + -3r Reorder the terms: 1 + 8r = 29 + 7r + -3r Combine like terms: 7r + -3r = 4r 1 + 8r = 29 + 4r Solving 1 + 8r = 29 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 1 + 8r + -4r = 29 + 4r + -4r Combine like terms: 8r + -4r = 4r 1 + 4r = 29 + 4r + -4r Combine like terms: 4r + -4r = 0 1 + 4r = 29 + 0 1 + 4r = 29 Add '-1' to each side of the equation. 1 + -1 + 4r = 29 + -1 Combine like terms: 1 + -1 = 0 0 + 4r = 29 + -1 4r = 29 + -1 Combine like terms: 29 + -1 = 28 4r = 28 Divide each side by '4'. r = 7 Simplifying r = 7
| 6z+18-9=27 | | 5y-5y=-5 | | 22+k=29 | | 4x+3x=9 | | -3z+6z=9z+9-4z | | ln(x)=ln(2)+ln(x-8) | | 5x+28=14x-36 | | 12x-3=3(2x+5) | | -1+3x=10 | | 1ov=60 | | y+y=5 | | 14q+14q+3p-1q= | | 9x-1/4y=5 | | 1/2w +2 = 4 | | 52-9=16 | | 3x^2+18x+81=25 | | ((a+4)/3a)-((2-4a)/6a) | | (a+4)/3a-(2-4a)/6a | | -16x^2-22x+100=62 | | (a+4)/(3*a)-(2-4*a)/(6*a) | | 14a^2/2a-8a | | 5x+20=100 | | 2n+8n-19=81 | | (-2y)-(4x)=20 | | 3x^2-4=4 | | 2x+25=25 | | x-0.6x=32 | | sqrt(2x)+13=5 | | x+2x+14=166 | | x-6=2/3+12 | | 5x-48+7x=-12 | | 9m+19m=84 |